Bosques nativos, servicios ecosistémicos culturales y cambio climático: Interrelaciones en el ámbito legal Argentino-Chileno (Papeles, 2021)
The purpose is to analyze regulation and public policies about cultural ecosystem services, native forests, biodiversity and climate change in Argentina and Chile.